Karakterisasi dan Pengaruh Waktu Polimerisasi terhadap Sifat Fisik dan Efisiensi Dye Sensitized Solar Cell (DSSC) Berbasis Poli Kuersetin - Fisyabilillah, Dea; Hardeli, Hardeli (Journal of Natural Sciences, 2024)
Dye-sensitized solar cells (DSSCs) are solar cells that use dye to absorb photons from sunlight, which are then converted into electrical energy. In this study, quercetin, a flavonoid dye, was polymerized to increase the number of conjugated bonds, thereby enhancing the efficiency of the DSSCs produced. The aim of this research is to determine how polymerization time of polyquercetin affects the energy conversion efficiency of the DSSCs. The polymerized quercetin was characterized using FTIR, density, and viscosity measurements. FTIR results indicated the presence of functional groups such as O-H phenol, C=O carbonyl, C=C aromatic, and C-O, confirming the occurrence of polymerization. The polymerized quercetin was measured with a multimeter, revealing an optimal efficiency of 19.5% at a polymerization time of 45 minutes. Density and viscosity tests provided a molecular weight of polyquercetin of 20,117.3804 g/mol, resulting in a degree of polymerization of 66.56 polyquercetin chains.